THE EFFECT OF INCENTIVES, WORK MOTIVATION, AND WORK STRESS ON THE PERFORMANCE OF GRABBIKE DRIVERS IN BEKASI - Edward Efendi Silalahi; Rohman Nul Karim; Tyna Yunita (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to determine whether incentives, work motivation, and work stress affect the performance of grabbike drivers in Bekasi. This research is a quantitative research with grabbike drivers as subjects and objects in Bekasi. The sampling technique used accidental sampling with a total sample of 90 respondents. using the SPSS 22 statistical tool. The results of this study provide an explanation that the incentive variable has a positive effect on the performance of grabbike drivers, work motivation has a positive effect on the performance of grabbike drivers and work stress has a negative effect on the performance of grabbike drivers. Then simultaneously the variables of incentives, work motivation, and work stress affect the performance of grabbike drivers.